Developing worksheet on mathematical modeling for financial literation using social arithmetics. (March 2020) - Suendang, T; Darmawijoyo
Abstract: This study aims to: (1) Produce Student Worksheets on Financial Literacy based on valid and practical Mathematical Modeling subject of Social Arithmetic, and (2) Find out the potential effects on learning outcomes from the development of Student Worksheets Financial Literacy based on Mathematical Modeling the subject of Social Arithmetic. This type of research used is the Design Research Development Study type. The subjects of this study were eighth grade students of SMA Negeri 2 Tungkal Ilir. Data collection techniques are by walk through, documents, tests, questionnaires, and interviews. The results of this study are: (1) This research has produced a Student Literature Worksheet based on Mathematical Modeling based on valid and practical Social Arithmetic subjects. (2) Student Worksheets Mathematical Modeling-based Financial Literacy developed has a potential effect on learning outcomes.